2021
DOI: 10.1186/s13023-021-02075-x
|View full text |Cite
|
Sign up to set email alerts
|

1H-NMR-based metabolic profiling identifies non-invasive diagnostic and predictive urinary fingerprints in 5q spinal muscular atrophy

Abstract: Background 5q spinal muscular atrophy (SMA) is a disabling and life-limiting neuromuscular disease. In recent years, novel therapies have shown to improve clinical outcomes. Yet, the absence of reliable biomarkers renders clinical assessment and prognosis of possibly already affected newborns with a positive newborn screening result for SMA imprecise and difficult. Therapeutic decisions and stratification of individualized therapies remain challenging, especially in symptomatic children. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Apart from the SMN2 copy number and less frequent genetic modifiers [11,12], only few laboratory biomarkers such as neurofilaments (peripheral neurofilament light chain [pNF-L], peripheral neurofilament heavy chain [pNF-H]) are available for SMA with early onset [13]. No longitudinal changes under nusinersen treatment were identified by extensive analyses of the metabolome in urine, serum, and cerebrospinal fluid (CSF) [14,15]. Cathepsin D is a lysosomal aspartyl protease that is highly expressed in the central nervous system as well as skeletal and cardiac muscle (Figure S1) and is involved in lysosomal degeneration of proteins [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the SMN2 copy number and less frequent genetic modifiers [11,12], only few laboratory biomarkers such as neurofilaments (peripheral neurofilament light chain [pNF-L], peripheral neurofilament heavy chain [pNF-H]) are available for SMA with early onset [13]. No longitudinal changes under nusinersen treatment were identified by extensive analyses of the metabolome in urine, serum, and cerebrospinal fluid (CSF) [14,15]. Cathepsin D is a lysosomal aspartyl protease that is highly expressed in the central nervous system as well as skeletal and cardiac muscle (Figure S1) and is involved in lysosomal degeneration of proteins [16].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the SMN2 copy number and less frequent genetic modifiers [11,12], only few laboratory biomarkers such as neurofilaments (peripheral neurofilament light chain [pNF‐L], peripheral neurofilament heavy chain [pNF‐H]) are available for SMA with early onset [13]. No longitudinal changes under nusinersen treatment were identified by extensive analyses of the metabolome in urine, serum, and cerebrospinal fluid (CSF) [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Whole metabolome. Urinary metabolic profiles successfully differentiated SMA patients from HCs with 81% sensitivity and 98% specificity [55]. Another study showed that even 59 plasma metabolites and 44 urine metabolites correlated with the MHFMS scores [34].…”
Section: Diagnosis and Prognosis Of Sma Using Molecular Biomarkersmentioning
confidence: 97%
“…43 In a more complex disease like spinal muscular atrophy SMA1 (OMIM 253300), 1 H-NMR-based metabolic profiling identifies biomarkers for diagnosis and treatment monitoring for an otherwise fatal neuromuscular disease, as shown recently. 44…”
Section: Untargeted Metabolomic Studiesmentioning
confidence: 99%